Simulasi Penghitungan Online Kredit Pemilikan Rumah Bank Xyz Berbasis Web di Portal Finansial www.kontan.co.id - Sano, Albert V. Dian (ComTech: Computer, Mathematics and Engineering Applications, 2013)
The objective of this study is to develop an online application of mortgage loan simulation. This application is developed based on a web application in order to be accessible anywhere and anytime. This application is expected to help prospective property’s consumers calculate their financial plans related to decisions concerning the amount of down payment, loan term, and the mortgage system model to be selected. There are two models of mortgage in this application. The first is a fixed and cap rate of interest, with the first three years of the mortgage interest rate of 9.75%, the fourth and fifth year interest of 10%, and the sixth year onwards using a rate cap interest with the indication of 12%. The second model is a 2-year fixed rate mortgage with the first two years rate of 8.5% and the third year onwards using adjustable rate mortgage of interest with the indication of 12%. Calculation formula and the interest rates in this application are obtained from Bank XYZ which is in turn applied in collaboration with financial portal www.kontan.co.id. This application has been tested by over 1000 users and the results are well proven and valid.